Reactivity of Tungsten-aryloxides with Hydrosilane Cocatalysts in Olefin Metathesis - Baibich, Ione M.; Kern, Carla [UNESP] (Sociedade Brasileira de Química, 2002)
As reatividades dos sistemas [WCl4(OAr)2] (OAr = O-2,6-C3H3Cl2, O-2,6-C6H3F2 e O-C6H3Me2), juntamente com os compostos de silício Ph2SiH2 e polimetilidrosiloxano (PMHS), foram estudadas em reações de metátese. As olefinas usadas foram 10-undecenoato de metila e 1-hexeno. Os resultados mostraram que os sistemas [WCl4(OAr)2]-composto de silício são ativos e seletivos quando os ligantes arilóxidos possuem grupos eletronegativos em suas estruturas. O composto de silício PMHS apresentou os melhores resultados, mesmo com o composto [WCl4(O-2,6-C6H3Me 2)2], que não possui substituintes eletronegativos. Por ser não-tóxico, não-volátil, barato e de fácil manuseio, PMHS é uma boa alternativa como cocatalisador em reações de metátese.

The reactivity of the [WCl4(OAr)2] (OAr = O-2,6-C3H3Cl2, O-2,6-C6H3F2 and O-C6H3Me2) systems, plus the silicon compounds Ph2SiH2 and polymethylhydrosiloxane (PMHS), were studied in metathesis reactions. The olefins used were methyl-10-undecenoate and 1-hexene. The results showed that the [WCl4(OAr)2]-silicon compound systems are active and selective when the aryloxide ligand contain electronegative groups. The silicon compound PMHS proved to be the best cocatalyst for metathesis, even with the [WCl4(O-2,6-C6H3Me 2)2] compound, which has no electronegative substituents. Because it is non-toxic, non-volatile, easy to handle and cheap, PMHS is a good alternative cocatalyst in metathesis reactions.
Keywords: tungsten catalysts; hydrosilane cocatalysts; olefin metathesis